Failure of bolt support and experimental study on the parameters of bolt-grouting for supporting the roadways in deep coal seam. (October 2017) - Pan, R.; Wang, Q.; Jiang, B.; Li, S.C.; Sun, H.B.; Qin, Q.; Yu, H.C.; Lu, W.
Abstract: This paper aims to provide some useful guidance for the design of parameters in bolt-grouting support and stabilize the surrounding rock in deep coal seam. A grouting reinforcement effect evaluation test instrument for fractured rock mass was developed. A laboratory test was carried out, the results show that the influence of water cement ratios on the grouting reinforcement effect was different, and the engineering proposals were put forward for the selection of water cement ratios. A field test was conducted for the selection of length and inter-row spacing of grouting bolt, the results show that the overall increase trend of pullout forces of common bolts was "Below > Right side > Above" under the condition of the same distance from grouting bolt, and the effective reinforcement range of grouting bolt had an important significance for the selection of parameters of grouting bolt. A successful field application was implemented, and the field test was verified as a good solution in the design of bolt-grouting parameters. Graphical abstract: Highlights: A test instrument was developed. A test on grouting effect was carried out. A field test on grouting bolt was conducted.